Trends Of Media Professionals In Syrian Media Institutions Towards Adopting And Using Artificial Intelligence Applications. (Damascus University Journal of arts and humanities sciences, 2026)
The study aimed to identify the trends of Syrian media professionals in Syrian media institutions towards adopting and using artificial intelligence technologies and applications. To achieve this, the researcher used the descriptive-survey method and a questionnaire consisting of standard declarative questions and phrases that were applied to a sample of (80) media professionals who were drawn using the available sample method. The results of the study showed that only 27.5% of the respondents use artificial intelligence applications by relying on a very limited number of them, and that the trends of media professionals towards adopting and using artificial intelligence applications are positive at a rate of 67.7%. The most important obstacles and reasons for not using artificial intelligence applications bySyrian media professionals are subjective reasons and obstacles related to the media professionals, such as their lack of skills to use modern technologies at a rate of 100%, and the lack of desire of most Syrian media professionals to use them at a rate of 84.4%, and objective reasons and obstacles related to media institutions, such as: the high financial cost of using artificial intelligence applications at a rate of 96.5%, and then the lack of encouragement by the management of media institutions for Syrian media professionals to use artificial intelligence applications at a rate of 79.3%. The study revealed no statistically significant differences between the average scores of Syrian media professionals regarding their trends toward adopting and using AI applications in Syrian media institutions based on demographic factors (gender, educational attainment, and years of experience). 70 % of respondents also had a positive view of the future adoption and use of AI technologies. Among the study's recommendations are that Syrian media institutions embrace a culture of AI, particularly by leveraging academic research, encouraging decision-makers to adopt and use AI technologies in the media, and working to eradicate digital media illiteracy among Syrian media professionals through specialized training.
Keywords: Trends; Syrian Media Professionals; Artificial Intelligence Applications; Syrian Media Institutions